Evaluation of rice cultivars for utilization of calcium and magnesium in the cerrado soil - Fageria, Nand Kumar; Morais, Orlando Peixoto (Pesquisa Agropecuaria Brasileira, 2014)
Forty eight upland rice (Oryza sativa L.) cultivars were evaluated for their response to lime in a greenhouse experiment using a Dark-Red Latosol. Based on a calibration curve, four levels of lime were applied (0, 9, 18 27 g/pot-lime neutralizing value 100%). These lime levels correspond to 1; 2.7; 4.2 and 5.4 meq/100 g of Ca + Mg in the soil. Yield increase for each cultivar was calculated at 9, 18 and 27g lime treatments in relation to production at no lime treatment. Rice cultivars responded to lime application and the response varied from cultivar to cultivar. Based on this yield increase, cultivars were classified in three groups as low, medium and highly responsive to lime application. Among tested cultivars, IAC 47 and CNA 104-B-68-B-2 were more productive at low as well as higher levels of Ca + Mg.